Water-based acrylate composite adhesive emulsion, water-based propionate composite adhesive and preparation method of water-based acrylate composite adhesive
By using non-reactive and reactive emulsifiers, soft and hard monomers and self-crosslinked monomers in aqueous acrylate composite glue, the problems of low bond strength and poor water resistance in existing aqueous composite glues are solved, and better moisture and heat resistance and bonding properties are achieved.
Patent Information
- Application Number
- CN202411841537.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-13
- Publication Date
- 2025-03-07
AI Technical Summary
The existing aqueous acrylate composite glue has low bond strength and poor water resistance, which affects its bonding performance on different materials.
By emulsifying and modifying the polyurethane resin and acrylate copolymer by using both non-reactive emulsifiers and reactive emulsifiers, combining soft monomers and hard monomers, and introducing self-crosslinking monomers and isocyanate curing agents, the crosslinking degree and high temperature resistance of the composite glue are improved.
It significantly improves the moisture and heat resistance and bonding strength of aqueous acrylate composite glue, meets the bonding needs of different types of materials, and improves the high temperature and steaming resistance of composite glue.
Smart Images

Figure CN119570405A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of acrylate composite adhesives, and in particular to a water-based acrylate composite adhesive latex, a water-based propionate composite adhesive and a preparation method thereof. Background Art
[0002] At present, the steam-resistant composite adhesives on the market are basically solvent-based polyurethanes, which have strong polarity and chemically active groups, high strength after cross-linking, and good adhesion to a variety of substrates. However, since solvent-based polyurethanes contain a large amount of organic solvents, they are flammable, explosive, volatile, have a strong odor, pollute the environment, and are toxic. Therefore, as people pay more and more attention to the sanitation and safety of packaging materials and environmental protection, green and environmentally friendly solvent-free laminating adhesives are increasingly valued as a substitute for solvent-based laminating adhesives. Water-based acrylic composite adhesives do not contain solvents and are green and environmentally friendly, but most water-based acrylic composite adhesives are synthesized from non-reactive emulsifiers. Although non-reactive emulsifiers have strong emulsification ability, they are easy to migrate to the surface of the film to form a weak interface layer, which leads to a decrease in the bonding strength of water-based acrylic composite adhesives and poor water resistance and moisture and heat resistance.
[0003] It can be seen that the existing technology still needs to be improved and enhanced. Summary of the invention
[0004] The purpose of the present invention is to provide a water-based acrylic composite adhesive latex, a water-based propionate composite adhesive and a preparation method, aiming to solve the problems of low bonding strength and poor water resistance of the existing water-based acrylic composite adhesive.
[0005] To achieve the above object, the solution provided by the present invention is:
[0006] The present invention provides an aqueous acrylic composite latex, comprising the following components in parts by weight:
[0007] 450-520 parts of deionized water, 250-300 parts of soft monomer, 119-215 parts of hard monomer, 45-55 parts of polyurethane resin, 5.0-5.5 parts of reactive emulsifier, 1-11 parts of non-reactive emulsifier, 1.5-10.5 parts of self-crosslinking monomer, and 3.25-3.34 parts of initiator.
[0008] Optionally, the non-reactive emulsifier includes at least one of sodium dodecyl sulfate, sodium dodecylbenzene sulfonate, sodium dodecyl diphenyl ether disulfonate, and disodium alkyl polyoxyethylene ether monoester sulfonate.
[0009] Optionally, the reactive emulsifier includes at least one of sodium allyloxyhydroxypropane sulfonate, sodium 2-acrylamido-2-methylpropane sulfonate, and ammonium allyloxyisomeric alcohol ether sulfate.
[0010] Optionally, the soft monomer includes at least one of butyl acrylate and isooctyl acrylate.
[0011] Optionally, the hard monomer includes at least one of methyl methacrylate, hydroxyethyl methacrylate, acrylonitrile, styrene, and acrylic acid.
[0012] Optionally, the self-crosslinking monomer includes at least one of diacetone acrylamide, adipic acid dihydrazide, methoxymethyl acrylamide, butoxymethyl acrylamide, acetoacetoxyethyl methacrylate, and a silane coupling agent.
[0013] Optionally, the initiator includes at least one of ammonium persulfate and ammonium bicarbonate.
[0014] The present invention also provides a method for preparing the aqueous acrylate composite latex, comprising the following steps:
[0015] S001. Add deionized water, polyurethane resin, non-reactive emulsifier, reactive emulsifier, and initiator to the reactor, or add deionized water, polyurethane resin, and non-reactive emulsifier to the reactor, stir and mix to obtain a base liquid;
[0016] S002. The soft monomer, the hard monomer, the reactive emulsifier or the reactive emulsifier and the non-reactive emulsifier, the self-crosslinking monomer and the deionized water are mixed and emulsified at high speed to obtain a stable monomer emulsion;
[0017] S003. The initiator and deionized water were stirred and mixed, and initiator solution A, initiator solution B, and initiator solution C were configured;
[0018] S004. The reactor was heated to 65 to 75 ° C, and then 5% of the total weight of the monomer emulsion was added to the reactor, and the mixture was stirred and mixed evenly;
[0019] S005. After stirring and mixing in step S004, initiator solution A is added to the reactor, and then the reactor temperature is raised to 75 to 85°C, and then initiator solution B and the remaining monomer emulsion are added to the reactor;
[0020] S006. After the initiator solution B and the remaining monomer emulsion are added, the initiator solution C is added;
[0021] S007. After the initiator solution C is added, the temperature is kept at 85°C for 2h;
[0022] S008. After the insulation is completed, the temperature of the reactor is lowered to 40°C, a pH adjuster is added to adjust the pH to 7.5-8.5, and then an aqueous solution containing a self-crosslinking monomer is added or not, and the aqueous solution containing a self-crosslinking monomer is evenly stirred to obtain an aqueous acrylate composite latex.
[0023] The present invention also provides a water-based acrylic composite adhesive, comprising the following components in parts by weight:
[0024] The aqueous acrylic composite latex comprises 100 parts, tackifying resin 25-30 parts, deionized water 0-10 parts, isocyanate curing agent 0-5 parts, wetting agent 0.5 parts and defoaming agent 0.1 parts.
[0025] Optionally, the tackifying resin includes at least one of rosin, terpene phenolic resin, and aldehyde ketone resin.
[0026] The beneficial effects of the present invention are:
[0027] The present invention provides a water-based acrylic composite adhesive latex, which can reduce the influence of the non-reactive emulsifier easily migrating to the surface of the adhesive film and causing the composite adhesive to have poor water resistance and moisture and heat resistance by using a non-reactive emulsifier and a reactive emulsifier to emulsify and modify the polyurethane resin and the acrylic copolymer, thereby improving the moisture and heat resistance of the water-based acrylic composite adhesive. By using a combination of a soft monomer and a hard monomer, the glass transition temperature of the provided water-based acrylic composite adhesive latex meets the requirements of the composite adhesive for bonding different types of materials. In addition, by introducing a self-crosslinking monomer into the latex, the crosslinking degree of the polymer is further increased, so that the high temperature resistance and boiling resistance of the water-based acrylic composite adhesive latex and the composite adhesive made from the latex are significantly increased.
[0028] The present invention also provides a method for preparing an aqueous acrylate composite latex. The method adopts a pre-emulsification dropwise polymerization method, and the reaction process is mild, which is beneficial to controlling the quality of the aqueous acrylate composite latex.
[0029] The present invention also provides a water-based acrylic composite adhesive, including a water-based acrylic emulsion. By using an isocyanate curing agent as an external cross-linking agent in combination with the water-based acrylic emulsion, the self-cross-linking monomer in the emulsion and the external cross-linking agent can be coordinated to improve the temperature resistance, cooking resistance and other properties of the water-based acrylic composite adhesive. By using a tackifying resin in the composite adhesive, the wetting adhesion of the composite adhesive to the material can be improved, so that the bonding strength of the water-based acrylic composite adhesive can be significantly improved. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] Figure 1 The present invention is a flow chart of a method for preparing a water-based acrylic composite latex. DETAILED DESCRIPTION
[0031] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0032] The present invention provides an aqueous acrylic composite latex, comprising the following components in parts by weight:
[0033] 450-520 parts of deionized water, 250-300 parts of soft monomers, 119-215 parts of hard monomers, 45-55 parts of polyurethane resin, 5.0-5.5 parts of reactive emulsifiers, 1-11 parts of non-reactive emulsifiers, 1.5-10.5 parts of self-crosslinking monomers, and 3.25-3.34 parts of initiators. The initiator includes at least one of ammonium persulfate and ammonium bicarbonate.
[0034] In the above composition, the polyurethane resin is homemade, and the preparation method can refer to CN109251705A. The polyurethane resin is a commonly used resin raw material in the composite glue. When it is introduced into the composite glue made of emulsion or emulsion, it can achieve firm bonding with various materials (such as metal, wood, plastic, etc.), thereby ensuring the bonding effect of the composite glue. The non-reactive emulsifier can be used alone or in combination with a reactive emulsifier to emulsify and modify the polyurethane resin, so that the modified polyurethane resin can be stably present in deionized water and maintain good dispersibility. The reactive emulsifier can be polymerized on the main chain of the polyurethane resin and the acrylate copolymer, with little residue, and can improve the water resistance, moisture and heat resistance and adhesion of the acrylate composite glue, but the emulsification ability of the reactive emulsifier is weak. Although non-reactive emulsifiers have strong emulsifying ability, they easily migrate to the surface of the film to form a weak interface layer. Therefore, the present invention compounded reactive emulsifiers and non-reactive emulsifiers to reduce the effect of the non-reactive emulsifier easily migrating to the surface of the film, which causes the composite adhesive to have poor water resistance and moisture and heat resistance.
[0035] In the above composition, the soft monomer can give the emulsion or the composite adhesive made of the emulsion good flexibility and elasticity; and the hard monomer can give the emulsion or the composite adhesive made of the emulsion certain water resistance, salt resistance and gloss. The joint use of soft and hard monomers can construct the skeleton of the water-based acrylic composite adhesive latex, which is convenient for further polymerization reaction to obtain the water-based acrylic composite adhesive latex, and the obtained water-based acrylic composite adhesive latex has good film-forming properties, so that the composite adhesive made of the emulsion has excellent bonding strength to the materials to be composited.
[0036] In addition, through the joint action of soft and hard monomers, a water-based acrylic composite adhesive latex can be constructed whose glass transition temperature (Tg) meets the use requirements of the composite adhesive, so that the water-based acrylic composite adhesive can be compositely bonded to different types of materials, such as paper and plastic, plastic and plastic, and metal and metal.
[0037] In the above composition, the self-crosslinking monomer can undergo crosslinking reaction with the acrylate copolymer and the polyurethane resin, further improving the crosslinking degree of the polymer, so that the high temperature resistance and cooking resistance of the water-based acrylate composite rubber latex and the composite rubber made from the latex can be increased.
[0038] Optionally, the non-reactive emulsifier includes at least one of sodium dodecyl sulfate, sodium dodecylbenzene sulfonate, sodium dodecyl diphenyl ether disulfonate, and disodium succinate alkyl polyoxyethylene ether monoester sulfonate. The above-mentioned non-reactive emulsifier has a hydrophilic sulfate group or sulfonic acid group and a hydrophobic alkyl group. This structure enables the non-reactive emulsifier to play a bridging role between the water phase and the oil phase, and can effectively reduce the tension of the oil-water interface. Therefore, the emulsification ability of the above-mentioned non-reactive emulsifier is relatively strong. Preferably, the non-reactive emulsifier is disodium succinate alkyl polyoxyethylene ether monoester sulfonate.
[0039] Optionally, the reactive emulsifier includes at least one of sodium allyloxyhydroxypropane sulfonate, sodium 2-acrylamide-2-methylpropane sulfonate, and ammonium allyloxyisopropane sulfate. Among them, sodium allyloxyhydroxypropane sulfonate contains a carbon-carbon double bond in its molecular structure, and can copolymerize with the polymer monomer to become a part of the polymer; sodium 2-acrylamide-2-methylpropane sulfonate contains an amide group in its molecular structure, and the amide group has a double bond structure, so that the amide group can be bonded with the main chain of the polyurethane resin to form a stable polymer system; the molecular structure of ammonium allyloxyisopropane sulfate contains an allyl group, which can participate in the polymerization reaction of the monomer to form a stable polymer system, and thus is not easy to migrate to the surface of the film.
[0040] Preferably, the reactive emulsifier is sodium 2-acrylamide-2-methylpropane sulfonate or allyloxy isomeric alcohol ether sulfate ammonium salt. Both sodium 2-acrylamide-2-methylpropane sulfonate and allyloxy isomeric alcohol ether sulfate ammonium salt can be compounded with disodium succinic acid alkyl polyoxyethylene ether monoester sulfonate to form an effective synergistic effect, so that the water-based acrylic composite adhesive has good water resistance and moisture and heat resistance.
[0041] Optionally, the soft monomer includes at least one of butyl acrylate and isooctyl acrylate. Butyl acrylate and isooctyl acrylate can impart good flexibility and elasticity to the water-based acrylic composite adhesive emulsion and the composite adhesive prepared from the emulsion.
[0042] Optionally, the hard monomer includes at least one of methyl methacrylate, hydroxyethyl methacrylate, acrylonitrile, styrene, and acrylic acid. Hydroxyethyl methacrylate can also be used as a functional monomer, which can provide hydroxyl groups for the emulsion and the composite adhesive. When used, the hydroxyl groups can form hydrogen bonds with the surface of the material to be composited, which can give the composite adhesive a higher bonding strength.
[0043] It is understandable that the soft monomers and hard monomers mentioned above all have different glass transition temperatures (Tg). By selecting soft monomers and hard monomers with different Tg, water-based acrylic composite latexes with different Tg can be designed to meet the bonding requirements of different types of materials, such as paper and plastic, plastic and plastic, and metal and metal.
[0044] Optionally, the self-crosslinking monomer includes at least one of diacetone acrylamide, adipic acid dihydrazide, methoxymethyl acrylamide, butoxymethyl acrylamide, ethyl acetoacetate methacrylate, and a silane coupling agent. Preferably, the self-crosslinking monomer includes at least one of diacetone acrylamide, adipic acid dihydrazide, and a silane coupling agent.
[0045] The present invention also provides a method for preparing the aqueous acrylate composite latex, comprising the following steps:
[0046] S001. Add deionized water, polyurethane resin, non-reactive emulsifier, reactive emulsifier, and initiator to the reactor, or add deionized water, polyurethane resin, and non-reactive emulsifier to the reactor, stir and mix to obtain a base liquid;
[0047] S002. The soft monomer, the hard monomer, the reactive emulsifier or the reactive emulsifier and the non-reactive emulsifier, the self-crosslinking monomer and the deionized water are mixed and emulsified at high speed to obtain a stable monomer emulsion;
[0048] S003. The initiator and deionized water were stirred and mixed, and initiator solution A, initiator solution B, and initiator solution C were configured;
[0049] S004. The reactor was heated to 65 to 75 ° C, and then 5% of the total weight of the monomer emulsion was added to the reactor, and the mixture was stirred and mixed evenly;
[0050] S005. After stirring and mixing in step S004, initiator solution A is added to the reactor, and then the reactor temperature is raised to 75 to 85°C, and then initiator solution B and the remaining monomer emulsion are added to the reactor;
[0051] S006. After the initiator solution B and the remaining monomer emulsion are added, the initiator solution C is added;
[0052] S007. After the initiator solution C is added, the temperature is kept at 85°C for 2h;
[0053] S008. After the insulation is completed, the temperature of the reactor is lowered to 40°C, a pH adjuster is added to adjust the pH to 7.5-8.5, and then an aqueous solution containing a self-crosslinking monomer is added or not, and the aqueous solution containing a self-crosslinking monomer is evenly stirred to obtain an aqueous acrylate composite latex.
[0054] The preparation method provided by the present invention adopts a pre-emulsification dropwise polymerization method, and the reaction process is mild, which is beneficial to controlling the quality of the product.
[0055] The present invention also provides a water-based acrylic composite adhesive, comprising the following components in parts by weight:
[0056] The aqueous acrylic composite latex comprises 100 parts, tackifying resin 25-30 parts, deionized water 0-10 parts, isocyanate curing agent 0-5 parts, wetting agent 0.5 parts and defoaming agent 0.1 parts.
[0057] The isocyanate curing agent is introduced into the water-based acrylic composite adhesive as an external cross-linking agent (which can form an interpenetrating network structure), and can cooperate with the self-cross-linking monomer in the emulsion to improve the heat resistance and boiling resistance of the water-based acrylic composite adhesive. In addition, the isocyanate curing agent performs well in terms of environmental protection and has low toxicity under normal use conditions. The tackifying resin can improve the wet adhesion of the composite adhesive to the material, so that the composite adhesive has high bonding strength.
[0058] Optionally, the tackifying resin includes at least one of rosin, terpene phenolic resin, and aldehyde ketone resin.
[0059] In order to further illustrate the water-based acrylic composite latex, water-based propionate composite adhesive and preparation method prepared by the present invention, the following examples and comparative examples are provided.
[0060] Example 1
[0061] This embodiment provides an aqueous acrylic composite latex, comprising the following components in parts by weight:
[0062] 520 parts of deionized water, 50 parts of polyurethane resin, 300 parts of soft monomer (220 parts of butyl acrylate, 80 parts of isooctyl acrylate), 119 parts of hard monomer (70 parts of styrene, 35 parts of methyl methacrylate, 9 parts of hydroxyethyl methacrylate, 5.0 parts of acrylic acid), 7.0 parts of self-crosslinking monomer (diacetone acrylamide), 3.5 parts of self-crosslinking monomer (adipic acid dihydrazide), 5.5 parts of reactive emulsifier, 1.0 part of non-reverse emulsifier, 1.2 parts of initiator (ammonium bicarbonate), 2.05 parts of initiator (ammonium persulfate).
[0063] Wherein, the non-reactive emulsifier is disodium alkyl polyoxyethylene ether monoester sulfonate.
[0064] The reactive emulsifier is allyloxy isomeric alcohol ether sulfate ammonium salt.
[0065] This embodiment also provides a method for preparing an aqueous acrylic composite latex, comprising the following steps:
[0066] S001. Add 300 parts of deionized water, 50 parts of polyurethane resin, 1.0 parts of disodium succinate alkyl polyoxyethylene ether monoester sulfonate, 0.5 parts of allyloxy isomeric alcohol ether sulfate ammonium salt, 1.2 parts of ammonium bicarbonate to the reactor, stir and mix to obtain a base liquid;
[0067] S002. 220 parts of butyl acrylate, 80 parts of isooctyl acrylate, 70 parts of styrene, 35 parts of methyl methacrylate, 9 parts of hydroxyethyl methacrylate, 5 parts of acrylic acid, 5 parts of allyloxy isocyanate sulfate, 7.0 parts of diacetone acrylamide and 150 parts of deionized water were mixed and emulsified at high speed for 30 min to obtain a stable monomer emulsion;
[0068] S003. 0.5 parts of ammonium persulfate and 10 parts of deionized water were stirred and mixed to prepare initiator solution A, 1.25 parts of ammonium persulfate and 40 parts of deionized water were stirred and mixed to prepare initiator solution B, 0.3 parts of ammonium persulfate and 10 parts of deionized water were stirred and mixed to prepare initiator solution C;
[0069] S004. The reactor was heated to 70 ° C, and then 5% of the total weight of the monomer emulsion was added to the reactor, and the mixture was stirred and mixed evenly;
[0070] S005. After stirring and mixing in step S004, initiator solution A is added to the reactor, and then the reactor temperature is raised to 75 to 85°C, and then initiator solution B and the remaining monomer emulsion are added to the reactor;
[0071] S006. After the initiator solution B and the remaining monomer emulsion are added, the initiator solution C is added;
[0072] S007. After the initiator solution C is added, the temperature is kept at 85°C for 2h;
[0073] S008. After the insulation is completed, the temperature of the reactor is lowered to 40°C, a pH adjuster is added to adjust the pH to 7.5-8.5, and then an aqueous solution containing adipic acid dihydrazide (the aqueous solution contains 10 parts by weight of deionized water) is added, and after stirring evenly, an aqueous acrylate composite latex with a solid content of 45% and a Tg of -20°C is obtained.
[0074] Example 2
[0075] This embodiment provides an aqueous acrylic composite latex, comprising the following components in parts by weight:
[0076] 450 parts of deionized water, 50 parts of polyurethane resin, 250 parts of soft monomer (butyl acrylate), 215 parts of hard monomer (120 parts of methyl methacrylate, 75 parts of acrylonitrile, 15 parts of hydroxyethyl methacrylate, 5 parts of acrylic acid), 1.5 parts of self-crosslinking monomer (silane coupling agent), 5.0 parts of reactive emulsifier, 11 parts of non-reactive emulsifier, 2.34 parts of initiator (ammonium persulfate), 1.0 part of initiator (ammonium bicarbonate).
[0077] Wherein, the non-reactive emulsifier is disodium alkyl polyoxyethylene ether monoester sulfonate.
[0078] The reactive emulsifier is sodium 2-acrylamide-2-methylpropane sulfonate.
[0079] This embodiment also provides a method for preparing an aqueous acrylic composite latex, comprising the following steps:
[0080] S001. Add 250 parts of deionized water, 50 parts of polyurethane resin, 1.0 parts of disodium succinate alkyl polyoxyethylene ether monoester sulfonate to the reactor, stir and mix to obtain a base liquid;
[0081] S002. 250 parts of butyl acrylate, 120 parts of methyl methacrylate, 75 parts of acrylonitrile, 15 parts of hydroxyethyl methacrylate, 5 parts of acrylic acid, 10 parts of allyloxy isomeric alcohol ether sulfate ammonium salt, 5 parts of sodium 2-acrylamido-2-methylpropane sulfonate, 1.5 parts of a silane coupling agent and 140 parts of deionized water were mixed and emulsified at high speed for 30 minutes to obtain a stable monomer emulsion;
[0082] S003. 0.7 parts of ammonium persulfate and 10 parts of deionized water were stirred and mixed to prepare initiator solution A, 1.34 parts of ammonium persulfate, 1.0 parts of ammonium bicarbonate and 40 parts of deionized water were stirred and mixed to prepare initiator solution B, 0.3 parts of ammonium persulfate and 10 parts of deionized water were stirred and mixed to prepare initiator solution C;
[0083] S004. The reactor was heated to 70 ° C, and then 5% of the total weight of the monomer emulsion was added to the reactor, and the mixture was stirred and mixed evenly;
[0084] S005. After stirring and mixing in step S004, initiator solution A is added to the reactor, and then the reactor temperature is raised to 75 to 85°C, and then initiator solution B and the remaining monomer emulsion are added to the reactor;
[0085] S006. After the initiator solution B and the remaining monomer emulsion are added, the initiator solution C is added;
[0086] S007. After the initiator solution C is added, the temperature is kept at 85°C for 2h;
[0087] S008. After the insulation is completed, the temperature of the reactor is lowered to 40°C, a pH adjuster is added to adjust the pH to 7.5-8.5, and after stirring evenly, an aqueous acrylic composite latex with a solid content of 50% and a Tg of 0°C is obtained.
[0088] Comparative Example 1
[0089] This comparative example provides an aqueous acrylic composite latex, comprising the following components in parts by weight:
[0090] 520 parts of deionized water, 50 parts of polyurethane resin, 300 parts of soft monomer (220 parts of butyl acrylate, 80 parts of isooctyl acrylate), 119 parts of hard monomer (70 parts of styrene, 35 parts of methyl methacrylate, 9 parts of hydroxyethyl methacrylate, 5.0 parts of acrylic acid), 7.0 parts of self-crosslinking monomer (diacetone acrylamide), 3.5 parts of self-crosslinking monomer (adipic acid dihydrazide), 6.5 parts of non-reverse emulsifier, 1.2 parts of initiator (ammonium bicarbonate), and 2.05 parts of initiator (ammonium persulfate).
[0091] Wherein, the non-reactive emulsifier is disodium alkyl polyoxyethylene ether monoester sulfonate.
[0092] This comparative example also provides a method for preparing an aqueous acrylic composite latex, comprising the following steps:
[0093] S001. Add 300 parts of deionized water, 50 parts of polyurethane resin, 1.5 parts of disodium succinate alkyl polyoxyethylene ether monoester sulfonate, 1.2 parts of ammonium bicarbonate to the reactor, stir and mix to obtain a base liquid;
[0094] S002. 220 parts of butyl acrylate, 80 parts of isooctyl acrylate, 70 parts of styrene, 35 parts of methyl methacrylate, 9 parts of hydroxyethyl methacrylate, 5 parts of acrylic acid, 5 parts of disodium succinate alkyl polyoxyethylene ether monoester sulfonate, 7.0 parts of diacetone acrylamide and 150 parts of deionized water were mixed and emulsified at high speed for 30 minutes to obtain a stable monomer emulsion;
[0095] S003. 0.5 parts of ammonium persulfate and 10 parts of deionized water were stirred and mixed to prepare initiator solution A, 1.25 parts of ammonium persulfate and 40 parts of deionized water were stirred and mixed to prepare initiator solution B, 0.3 parts of ammonium persulfate and 10 parts of deionized water were stirred and mixed to prepare initiator solution C;
[0096] S004. The reactor was heated to 70 ° C, and then 5% of the total weight of the monomer emulsion was added to the reactor, and the mixture was stirred and mixed evenly;
[0097] S005. After stirring and mixing in step S004, initiator solution A is added to the reactor, and then the reactor temperature is raised to 75 to 85°C, and then initiator solution B and the remaining monomer emulsion are added to the reactor;
[0098] S006. After the initiator solution B and the remaining monomer emulsion are added, the initiator solution C is added;
[0099] S007. After the initiator solution C is added, the temperature is kept at 85°C for 2h;
[0100] S008. After the insulation is completed, the temperature of the reactor is lowered to 40°C, a pH adjuster is added to adjust the pH to 7.5-8.5, and then an aqueous solution containing adipic acid dihydrazide (the aqueous solution contains 10 parts by weight of deionized water) is added, and after stirring evenly, an aqueous acrylate composite latex with a solid content of 45% is obtained.
[0101] Comparative Example 2
[0102] This embodiment provides an aqueous acrylic composite latex, comprising the following components in parts by weight:
[0103] 450 parts of deionized water, 50 parts of polyurethane resin, 250 parts of soft monomer (butyl acrylate), 215 parts of hard monomer (120 parts of methyl methacrylate, 75 parts of acrylonitrile, 15 parts of hydroxyethyl methacrylate, 5 parts of acrylic acid), 1.5 parts of self-crosslinking monomer (silane coupling agent), 11 parts of non-reactive emulsifier, 2.34 parts of initiator (ammonium persulfate), 1.0 part of initiator (ammonium bicarbonate).
[0104] Wherein, the non-reactive emulsifier is disodium alkyl polyoxyethylene ether monoester sulfonate.
[0105] This embodiment also provides a method for preparing an aqueous acrylic composite latex, comprising the following steps:
[0106] S001. Add 250 parts of deionized water, 50 parts of polyurethane resin, 1.0 parts of disodium succinate alkyl polyoxyethylene ether monoester sulfonate to the reactor, stir and mix to obtain a base liquid;
[0107] S002. 250 parts of butyl acrylate, 120 parts of methyl methacrylate, 75 parts of acrylonitrile, 15 parts of hydroxyethyl methacrylate, 5 parts of acrylic acid, 15 parts of allyloxy isomeric alcohol ether sulfate ammonium salt, 1.5 parts of silane coupling agent and 140 parts of deionized water were mixed and emulsified at high speed for 30 minutes to obtain a stable monomer emulsion;
[0108] S003. 0.7 parts of ammonium persulfate and 10 parts of deionized water were stirred and mixed to prepare initiator solution A, 1.34 parts of ammonium persulfate, 1.0 parts of ammonium bicarbonate and 40 parts of deionized water were stirred and mixed to prepare initiator solution B, 0.3 parts of ammonium persulfate and 10 parts of deionized water were stirred and mixed to prepare initiator solution C;
[0109] S004. The reactor was heated to 70 ° C, and then 5% of the total weight of the monomer emulsion was added to the reactor, and the mixture was stirred and mixed evenly;
[0110] S005. After stirring and mixing in step S004, initiator solution A is added to the reactor, and then the reactor temperature is raised to 75 to 85°C, and then initiator solution B and the remaining monomer emulsion are added to the reactor;
[0111] S006. After the initiator solution B and the remaining monomer emulsion are added, the initiator solution C is added;
[0112] S007. After the initiator solution C is added, the temperature is kept at 85°C for 2h;
[0113] S008. After the insulation is completed, the temperature of the reactor is lowered to 40°C, a pH adjuster is added to adjust the pH to 7.5-8.5, and after stirring evenly, an aqueous acrylic composite latex with a solid content of 50% and a Tg of 0°C is obtained.
[0114] In order to perform performance testing on the water-based acrylate composite adhesive provided by the present invention, the following water-based acrylate composite adhesive is provided.
[0115] The water-based acrylic composite adhesive A comprises the following components in parts by weight:
[0116] 100 parts of the water-based acrylic composite adhesive latex provided in Example 1, 25 parts of a tackifying resin (rosin), 0.2 parts of a wetting agent, and 0.1 parts of a defoaming agent are uniformly dispersed at high speed to obtain a water-based acrylic composite adhesive A.
[0117] The water-based acrylic composite adhesive B comprises the following components in parts by weight:
[0118] Comparative Example 1 provides 100 parts of the aqueous acrylic composite adhesive latex, 25 parts of a tackifying resin (rosin), 0.2 parts of a wetting agent, and 0.1 parts of a defoaming agent. The above composition is dispersed uniformly at high speed to obtain an aqueous acrylic composite adhesive B.
[0119] Performance test 1:
[0120] The peel strength (reflecting the bonding strength) and moisture and heat resistance of the water-based acrylic composite adhesive A and the water-based acrylic composite adhesive B were tested in accordance with the following method. The test results are shown in Table 1.
[0121] Water-based acrylic composite adhesive A, water-based acrylic composite adhesive B and commercially available water-based acrylic laminating adhesive were coated on non-corona-treated Bopp (biaxially oriented polypropylene film) film at 3-5g / m2, dried at 80°C for 1 min, and then laminated with white cardboard. The laminated adhesive was fully rolled and laminated (simulating paper-plastic lamination), and then left at room temperature for 24 hours to test the peel strength and moisture-heat resistance of the composite adhesive.
[0122] Table 1
[0123]
[0124] In Table 1, when the paper is broken, the peel strength cannot be measured, so it is not provided. From the test results in Table 1, it can be seen that the moisture and heat resistance of water-based acrylate composite adhesive A (containing the water-based acrylate composite adhesive emulsion provided in Example 1) is better than that of water-based acrylate composite adhesive B (containing the water-based acrylate composite adhesive emulsion provided in Comparative Example 1) and commercially available laminating adhesive. For water-based acrylate composite adhesive B, no reactive emulsifier is used in the emulsion, so its moisture and heat resistance is not as good as that of water-based acrylate composite adhesive A.
[0125] The water-based acrylic composite adhesive C comprises the following components in parts by weight:
[0126] 100 parts of the aqueous acrylate composite emulsion provided in Example 1, 25 parts of tackifying resin (terpene phenolic), 0.2 parts of wetting agent, 0.1 parts of defoaming agent, 0-3 parts of isocyanate (adjusted according to performance test requirements). The above composition is dispersed uniformly at high speed to obtain aqueous acrylate composite adhesive C.
[0127] The water-based acrylic composite adhesive D comprises the following components in parts by weight:
[0128] Comparative Example 1 provides 100 parts of aqueous acrylic composite emulsion, 25 parts of tackifying resin (terpene phenolic), 0.2 parts of wetting agent, 0.1 parts of defoaming agent, and 0-3 parts of isocyanate (adjusted according to performance test requirements). The above composition is dispersed uniformly at high speed to obtain aqueous acrylic composite glue D.
[0129] Performance Test 2
[0130] The peel strength and boiling resistance of water-based acrylic composite adhesive C and water-based acrylic composite adhesive D were tested according to the following method. The test results are shown in Table 2 (Table 2 corresponds to water-based acrylic composite adhesive C) and Table 3 (Table 3 corresponds to water-based acrylic composite adhesive D).
[0131] According to 5g / m 2 Water-based acrylic composite adhesive C, water-based acrylic composite adhesive D, and commercially available water-based acrylic laminating adhesive were coated on a non-corona-treated Bopp (biaxially oriented polypropylene film) film, dried at 100°C for 3 min, and then composited with a PET film (simulated plastic and plastic composite) or VMPET film (polyester aluminized film). The composite was fully rolled and aged at 55°C for 24 h, and the peel strength and cooking resistance (120°C, 3 min) of the composite adhesive were tested.
[0132] Table 2
[0133]
[0134] Table 3
[0135]
[0136] It can be seen from the test results in Table 2 and Table 3 that when the addition amount of isocyanate curing agent is 0, whether it is water-based acrylic composite adhesive C or water-based acrylic composite adhesive D, when compounding plastic films, the peel strength and high-temperature cooking resistance at room temperature are not as good as those of ordinary water-based composite adhesives on the market, indicating that the use of isocyanate curing agent can improve the heat resistance, cooking resistance, bonding strength and other properties of water-based acrylic composite adhesives.
[0137] After adding isocyanate curing agent, the peel strength and high temperature cooking resistance of water-based acrylic composite adhesive C at room temperature are better than those of water-based acrylic composite adhesive D. This is also because the emulsion used in water-based acrylic composite adhesive D does not use reactive emulsifiers.
[0138] The water-based acrylic composite adhesive E comprises the following components in parts by weight:
[0139] 100 parts of the aqueous acrylate composite emulsion provided in Example 2, 30 parts of tackifying resin (aldehyde-ketone resin), 10 parts of deionized water, 0.5 parts of wetting dispersant, 0.1 parts of defoaming agent, 0-5 parts of isocyanate curing agent (adjusted according to performance test requirements). The above composition is dispersed uniformly at high speed to obtain aqueous acrylate composite adhesive E.
[0140] The water-based acrylic composite adhesive F comprises the following components in parts by weight:
[0141] Comparative Example 2 provides 100 parts of water-based acrylic composite emulsion, 30 parts of tackifying resin (aldehyde-ketone resin), 10 parts of deionized water, 0.5 parts of wetting dispersant, 0.1 parts of defoaming agent, and 0-5 parts of isocyanate curing agent (adjusted according to performance test requirements). The above composition is dispersed uniformly at high speed to obtain water-based acrylic composite adhesive E.
[0142] Performance Test 3
[0143] The peel strength and temperature resistance of water-based acrylic composite adhesive E and water-based acrylic composite adhesive F were tested according to the following method. The test results are shown in Table 4 (Table 4 corresponds to water-based acrylic composite adhesive E) and Table 5 (Table 5 corresponds to water-based acrylic composite adhesive F).
[0144] Press 5~10g / m 2 Water-based acrylic composite adhesive E, water-based acrylic composite adhesive F, commercially available oily composite adhesive and commercially available ordinary water-based composite adhesive were coated on the copper foil film, dried at 100°C for 3 minutes, and then composited with aluminum foil. The composite was fully rolled and then aged at 50°C for 48 hours. The T-peel strength of the composite adhesive at room temperature, the T-peel strength after aging for 3 days at 60°C and 85% humidity, the double-sided heat resistance at 150°C, and the single-sided heat resistance at 190°C were tested.
[0145] Table 4
[0146]
[0147] Table 5
[0148]
[0149] It can be seen from the test results in Tables 4 and 5 that the water-based acrylic composite adhesive E is close to the level of the oil-based adhesive. The T-peel strength at room temperature, the T-peel strength after aging and the temperature resistance of the water-based acrylic composite adhesive are better than those of the water-based acrylic composite adhesive F. This is also because the emulsion used in the water-based acrylic composite adhesive F does not use a reactive emulsifier.
[0150] The above description is only a preferred embodiment of the present invention, and does not limit the patent scope of the present invention. All equivalent structural changes made by using the contents of the present invention specification and drawings under the inventive concept of the present invention, or directly / indirectly applied in other related technical fields are included in the patent protection scope of the present invention.
Claims
1. A water-based acrylic composite latex, characterized in that: The composition comprises the following parts by weight: 450-520 parts of deionized water, 250-300 parts of soft monomer, 119-215 parts of hard monomer, 45-55 parts of polyurethane resin, 5.0-5.5 parts of reactive emulsifier, 1-11 parts of non-reactive emulsifier, 1.5-10.5 parts of self-crosslinking monomer, and 3.25-3.34 parts of initiator.
2. The aqueous acrylate composite latex according to claim 1, characterized in that: The non-reactive emulsifier includes at least one of sodium dodecyl sulfate, sodium dodecylbenzene sulfonate, sodium dodecyl diphenyl ether disulfonate, and disodium succinic acid alkyl polyoxyethylene ether monoester sulfonate.
3. The aqueous acrylate composite latex according to claim 1, characterized in that: The reactive emulsifier includes at least one of sodium allyloxyhydroxypropane sulfonate, sodium 2-acrylamido-2-methylpropane sulfonate, and ammonium allyloxy isomeric alcohol ether sulfate.
4. The aqueous acrylate composite latex according to claim 1, characterized in that: The soft monomer includes at least one of butyl acrylate and isooctyl acrylate.
5. The aqueous acrylate composite latex according to claim 1, characterized in that: The hard monomer includes at least one of methyl methacrylate, hydroxyethyl methacrylate, acrylonitrile, styrene and acrylic acid.
6. The aqueous acrylate composite latex according to claim 1, characterized in that: The self-crosslinking monomer includes at least one of diacetone acrylamide, adipic acid dihydrazide, methoxymethyl acrylamide, butoxymethyl acrylamide, acetoacetoxyethyl methacrylate, and a silane coupling agent.
7. The aqueous acrylate composite latex according to claim 1, characterized in that: The initiator includes at least one of ammonium persulfate and ammonium bicarbonate.
8. A method for preparing the aqueous acrylate composite latex according to any one of claims 1 to 7, characterized in that: The following steps are involved: S001. Add deionized water, polyurethane resin, non-reactive emulsifier, reactive emulsifier, and initiator to the reactor, or add deionized water, polyurethane resin, and non-reactive emulsifier to the reactor, stir and mix to obtain a base liquid; S002. The soft monomer, the hard monomer, the reactive emulsifier or the reactive emulsifier and the non-reactive emulsifier, the self-crosslinking monomer and the deionized water are mixed and emulsified at high speed to obtain a stable monomer emulsion; S003. The initiator and deionized water were stirred and mixed, and initiator solution A, initiator solution B, and initiator solution C were configured; S004. The reactor was heated to 65 to 75 ° C, and then 5% of the total weight of the monomer emulsion was added to the reactor, and the mixture was stirred and mixed evenly; S005. After stirring and mixing in step S004, initiator solution A is added to the reactor, and then the reactor temperature is raised to 75 to 85°C, and then initiator solution B and the remaining monomer emulsion are added to the reactor; S006. After the initiator solution B and the remaining monomer emulsion are added, the initiator solution C is added; S007. After the initiator solution C is added, the temperature is kept at 85°C for 2h; S008. After the insulation is completed, the temperature of the reactor is lowered to 40°C, a pH adjuster is added to adjust the pH to 7.5-8.5, and then an aqueous solution containing a self-crosslinking monomer is added or not, and the aqueous solution containing a self-crosslinking monomer is evenly stirred to obtain an aqueous acrylate composite latex.
9. A water-based acrylic composite adhesive, characterized in that: Including the following weight parts composition: 100 parts of the aqueous acrylic composite latex according to any one of claims 1 to 7, 25 to 30 parts of a tackifying resin, 0 to 10 parts of deionized water, 0 to 5 parts of an isocyanate curing agent, 0.5 parts of a wetting agent, and 0.1 parts of a defoaming agent.
10. The water-based acrylate composite adhesive according to claim 9, characterized in that: The tackifying resin includes at least one of rosin, terpene phenolic resin and aldehyde ketone resin.
Citation Information
Patent Citations
Water-based aromatic polyurethane modified acrylic adhesive and preparation method thereof
CN109251705A
Cited By
Composite pressure-sensitive adhesive for protective film and preparation method of composite pressure-sensitive adhesive
CN120383898A
A composite pressure-sensitive adhesive for a protective film and a method for manufacturing the same
CN120383898B